Chemokine and cytokine levels in osteoarthritis and rheumatoid arthritis synovial fluid - Hampel, Ulrike; Sel, Saadettin (Journal of immunological methods, 2013)
To develop a method of the assay of chemokine and cytokine signaling in synovial fluid from patients suffering from osteoarthritis (OA) or rheumatoid arthritis (RA) and evaluate the effect of heterophilic antibodies on the reliability of the data. 21 synovial fluid samples from OA and 16 synovial fluid samples from RA patients were analyzed using a unique 2 step dot sandwich ELISA based micro-well protein array designed to detect heterophilic antibody signaling in the presence or absence of an effective heterophilic blocking reagent with assays carried out for Eotaxin, hGROa, interleukin (IL)-8, IP10, MCP-1, MCP-2, MIG, RANTES, TARC and IL-6. Array analysis reveals that the selective presence of heterophilic antibodies interferes with the accurate assay of synovial fluid samples from a minority of RA patients but not OA synovia. Using a commercial blocking diluent OA and RA synovial fluids reveal significant differences in chemokine content (IL-6, Eotaxin, hGROa, MCP-2, MIG, TARC, IL-8, RANTES). Using a two-step assay protocol it is possible to readily detect inappropriate antibody signaling due to heterophilic antibodies and devise a protocol designed to eliminate this problem thereby more accurately quantify cytokines and chemokines specific to both RA and OA fluids.